Study of Reaction Time to Visual Stimuli in Athletes with and without a Hearing Impairment. Issue 1 (August 2014) - Soto-Rey, Javier; Pérez-Tejero, Javier; Rojo-González, Jesús J.; Reina, Raúl
This study analyzes the differences in manual reaction time (RT) to visual stimuli in two samples of physically active persons: a group of athletes without hearing impairment ( n = 79; M age = 22.6yr., SD = 3.7) and a group of athletes with hearing impairment ( n = 44, M age = 25.6 yr., SD = 5.0). Reaction time (RT) was measured and then differences between both groups were assessed by sex, type of sport (individual vs team sports), and competition level. RT to visual stimuli was significantly shorter for athletes with hearing impairment than for those without hearing impairment, with a significant sex difference (shorter RT for males), but no differences regarding type of sport or competition level. Suggestions for further research and sport applications are provided.